Risk of obstetric anal sphincter tear among primiparous women with a history of female genital mutilation, giving birth in Sweden. - Bita Eshraghi; Jonas Hermansson; Vanja Berggren; Lena Marions (PLoS ONE, 2022)
Background Female genital mutilation (FGM) includes a range of procedures involving partial or total removal of the external female genitalia. It is a harmful procedure that violates human rights of girls and women. FGM has been associated with obstetric anal sphincter injury (OASI), among other adverse obstetric complications. However, the obstetric outcomes in high-income countries are not clear. The aim of this study was to compare the risk of OASI among primiparous women, with and without a history of FGM, giving birth in Sweden. Method A population-based cohort-study based on data from the Swedish Medical Birth Register during the period 2014-2018. The study included primiparous women with singleton term pregnancies. We compared the risk, using multivariable logistic regression, of our main outcome OASI between women with a diagnosis of FGM and women without a diagnosis of FGM. Secondary outcomes included episiotomy and instrumental vaginal delivery. Result A total of 239,486 primiparous women with a term singleton pregnancy were identified. We included 1,444 women with a diagnosis of FGM and 186,294 women without a diagnosis of FGM in our analysis. The overall rate of OASI was 3% in our study population. By using multivariable logistic regression analysis, we found that women with a diagnosis of FGM had a significantly increased odds ratio (OR) of OASI (OR 2.69, 95%CI: 2.14-3.37) compared to women without a diagnosis of FGM. We also found an association between FGM and instrumental delivery as well as the use of episiotomy. Conclusion Women with a history of FGM have an almost tripled risk of OASI in comparison with women without FGM, when giving birth in a Swedish setting. Increased knowledge and awareness regarding FGM, and its potential health implications is crucial in order to minimise the risk of OASI among women with FGM giving birth in high-income countries. A limitation in our study is the lack of information about the specific types of FGM.